2015
DOI: 10.1142/s0578563415400069
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Direct and Indirect Damages from Storm Surges: The Case of Hamburg—Wilhelmsburg

Abstract: This paper estimates the economic costs from storm surge scenarios in the Free and Hanseatic City of Hamburg. Hydrodynamic and damage models simulate the direct damages to residential and commercial buildings and equipment in a part of the city named Hamburg-Wilhelmsburg. They are assigned to individual economic sectors and then integrated into an economic model. This model accounts for the indirect impacts due to the interruption of production processes. Furthermore, the indirect costs are allocated to the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…For Hamburg, the wave conditions related to the storm surge scenarios are calculated with a numerical model [within SP3 of the project; see Ujeyl and Rose, 2015], which is also used to determine the storm surge water levels in the area of Hamburg. The calculated wave conditions are not considered for the statistical analyses for two reasons: first, no datasets for such analyses are available, and second, the estimated wave heights (and wave periods) are very small compared to the storm surge water levels due to the geographical location in an estuary.…”
Section: Storm Surges and Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…For Hamburg, the wave conditions related to the storm surge scenarios are calculated with a numerical model [within SP3 of the project; see Ujeyl and Rose, 2015], which is also used to determine the storm surge water levels in the area of Hamburg. The calculated wave conditions are not considered for the statistical analyses for two reasons: first, no datasets for such analyses are available, and second, the estimated wave heights (and wave periods) are very small compared to the storm surge water levels due to the geographical location in an estuary.…”
Section: Storm Surges and Wavesmentioning
confidence: 99%
“…The overall flood risk is then derived by multiplying the estimated failure probabilities with the potential losses in the hinterland Dassanayake et al, 2015;Ujeyl and Rose, 2015]. The paper is organized as follows: the observational datasets used for the model development are described in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated damages and the inundation depths are brought together using GIS-based spatial modeling (see Sec. 4) using the developed depth-damage functions [Ujeyl and Rose, 2015]. A comparative analysis with commonly used meso-scale approaches is also performed to underpin the benefit of the proposed approach (e.g.…”
Section: Key Resultsmentioning
confidence: 99%
“…The assessment of the direct economic losses has been performed at a micro-scale level and the losses were then aggregated to a meso-scale level by clustering similar buildings [see Ujeyl and Rose, 2015]. Although this approach required more data and efforts, it has been shown that better results were achieved as compared to the common meso-scale assessment.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…These input conditions were then used by Ujeyl and Rose [2015] who have run inundation models to estimate the flood extents and flood depths for each storm surge scenario in the pilot sites. From these simulations, they estimated both the direct and indirect economic consequences where especially the latter is an important contribution and shows the large variability of indirect economic consequences as compared to direct ones.…”
Section: About This Issuementioning
confidence: 99%